STRATEGI PEMASARAN J&C COOKIES MELALUI ANALISIS TOWS DALAM MENINGKATKAN DAYA SAING INDUSTRI KUE KERING - Fawwaz Jannuranti; Arisna Siti Marlina; Reigina Zahira Asshofa (CV. Denasya Smart Publisher, 2026)
The food industry, particularly the cookie sector, is growing rapidly as lifestyles evolve and consumers increasingly seek practical, innovative, and high-quality products. Using the TOWS analysis approach, this study aims to evaluate J&C Cookies’ marketing strategies in addressing competition within the cookie industry. The method used is qualitative descriptive, utilizing secondary data from company documents, marketing literature, and information on business strategies to examine the company’s internal and external aspects. Data analysis was conducted through data reduction, followed by the creation of a TOWS matrix to generate alternative marketing strategies. To enhance the company’s competitiveness in both local and international markets, the developed strategies include enhancing product reputation during festive occasions, creating new product variations, and expanding market distribution. These strategies are expected to strengthen J&C Cookies’ competitiveness in both local and global markets